WHY VOCABULARY IS IMPORTANT IN LANGUAGE USAGE - Mashxura Xakimova; Dilafruz Nematjanova (Web of Journals Publishing, 2024)
Resent research’s show that we need to understand at least 98% of the English words we see to understand what the discourse means. Improving learners’ vocabulary acquisition will help to improve comprehension of books and magazines. If a student is not an avid reader, they cannot have the necessary exposure to the academic teaxts with a high level vocabulary in context they will not develop their reading and writing skills.
Keywords: Resent research’s show that we need to understand at least 98% of the English words we see to understand what the discourse means. Improving learners’ vocabulary acquisition will help to improve comprehension of books and magazines. If a student is not an avid reader, they cannot have the necessary exposure to the academic teaxts with a high level vocabulary in context they will not develop their reading and writing skills.